2010
DOI: 10.1093/pcp/pcq057
|View full text |Cite
|
Sign up to set email alerts
|

UDP-Glucose Pyrophosphorylase is Rate Limiting in Vegetative and Reproductive Phases in Arabidopsis thaliana

Abstract: UDP-glucose pyrophosphorylase (UGPase) is an important enzyme in the metabolism of UDP-glucose, a precursor for the synthesis of carbohydrate cell wall components, such as cellulose and callose. The Arabidopsis thaliana genome contains two putative genes encoding UGPase, AtUGP1 and AtUGP2. These genes are expressed in all organs. In order to determine the role of UGPase in vegetative and reproductive organs, we employed a reverse genetic approach using the T-DNA insertion mutants, atugp1 and atugp2. Despite a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(106 citation statements)
references
References 53 publications
0
98
0
2
Order By: Relevance
“…Seed set is known to be especially dependent on metabolism (Lauxmann et al, 2016), and this trait was previously reported to be impaired in the double ugp1 ugp2 mutant (Meng et al, 2009;Park et al, 2010). The ugp1, vac-inv, and apl1 KO lines displayed shorter and aborted siliques ( Figure 5A) and a significant increase in seed abortion (P < 0.05; Figure 5B) in longday conditions (16-h photoperiod) compared with wild-type plants.…”
Section: Ko Lines Ugp1 Vac-inv and Apl1 Exhibit Seed Abortion Phenomentioning
confidence: 83%
“…Seed set is known to be especially dependent on metabolism (Lauxmann et al, 2016), and this trait was previously reported to be impaired in the double ugp1 ugp2 mutant (Meng et al, 2009;Park et al, 2010). The ugp1, vac-inv, and apl1 KO lines displayed shorter and aborted siliques ( Figure 5A) and a significant increase in seed abortion (P < 0.05; Figure 5B) in longday conditions (16-h photoperiod) compared with wild-type plants.…”
Section: Ko Lines Ugp1 Vac-inv and Apl1 Exhibit Seed Abortion Phenomentioning
confidence: 83%
“…There are at least nine clades of nucleotide sugar pyrophosphorylases ( Figure 1A), which have different activities and physiological functions (Kotake et al, 2010). UDP-Glc pyrophosphorylases generate UDP-Glc, the starting substrate of UDP-sugar metabolism, which is used for the synthesis of cellulose and b-1,3-glucan and for the b-1,4-glucan backbone of xyloglucan (Hayashi et al, 1987;Gordon and Maclachlan, 1989;Cocuron et al, 2007;Park et al, 2010). A plant-specific enzyme, UDP-sugar pyrophosphorylase (USP), converts various monosaccharide 1-Ps to their respective UDP-sugars in the salvage pathway and is required for pollen development (Kotake et al, 2004(Kotake et al, , 2007Schnurr et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…RT-PCR analysis Semiquantitative RT-PCR was performed according to Park et al (2010) with slight modifications. Briefly, mRNA was isolated from the tissues described in Plant Materials using a Fast Track 2.0 mRNA isolation kit (Invitrogen, San Diego, CA, USA).…”
Section: Plant Materialsmentioning
confidence: 99%
“…Plant transformation Plant transformation was performed according to Park et al (2006) and Park et al (2010). Briefly, transgenic Arabidopsis plants were generated with the Agrobacterium binary vector by the floral dip method (Clough and Bent, 1998).…”
Section: Construction Of Rnai Binary Vectorsmentioning
confidence: 99%